Investigating Uppsala Regional Alternative Food Networks - an explorative case study on Farmer-to-Wholesale Food Hubs - Chifamba, Veronica; Petri Cortés, Daniel (SLU/Dept. of Energy and Technology, 2022)
The sustainability crisis that conventional food systems are suffering worldwide has recently led Sweden and Uppsala County to publish reports on new food strategies. Solutions for the problems need collaborative efforts from a multiplicity of actors. This study dives into the role of Alternative Food Networks (AFNs) which offer substitutes to unsustainable food products sourced from industrialised conventional food systems. These networks have always existed, but are increasing in relevance in Sweden, especially in towns like Uppsala as reflected in consumption choices by citizens. However, different factors have made AFNs less relevant and less convenient than in other countries. Many types of initiatives and organisations form AFNs, this study looks at the relevance of a type of initiative called Food Hubs (FHs). A FH is an organisation that is responsible for the aggregation and/or distribution of food products in proximity with the goal of supporting local and regional economies. The aim is to investigate opportunities for the development of Food Hubs in the surroundings of Uppsala City, Sweden and use them to support the development of a sustainable food system in the region. The lack of academic knowledge regarding AFNs in this region resulted in the design of an explorative study. For that, we investigate relevant aspects for the potential formation of a FH by; investigating the attitudes that microenterprise producers and local wholesale buyers have towards this idea of a farmer to wholesale FH. The sample of wholesale buyers consist of a variety of food service actors and four local retailers which already are part of local AFNs or showed qualities that indicated their potential interest. The study also aims to identify some of the products and the approximated volumes that the participant farmers produced. The authors also collect data on the attitudes of the producers toward an increase in production and what their capacity could be if it was used to its full potential without changing their predominantly sustainable methods. Five research questions were formed to answer the above points. All this information was gathered through structured and semi structured interviews. The results show that many microenterprise farmers in the studied region produce mostly livestock and grains, but vegetable and fruit production also occur when the season arrives or in greenhouses. Their attitudes towards increase in production were to a greater extent negative since they felt content with the current models and were sceptical about the costs they would incur and the reliability of it. On the other hand, the wholesale buyers expressed more positive interest towards a FH as they were keen to support local food systems and had since it would theoretically provide local produce conveniently to them. However, they emphasised that they are not prepared to pay more, and that reliability is key for their involvement. FHs have been successful in some parts of the world like the US; hence their feasibility is also possible in Uppsala only if the hubs are able to create value for the actors in this region. Regardless of the negative attitudes towards collaborating with FH and increasing production, we saw many signs of food actors in AFNs who prioritize different values than the CFS.